PROFESSIONAL SKEPTICISM, INTEGRITY, AND AUDIT QUALITY: TIME BUDGET PRESSURE AS A MODERATOR - Fariz Zulham; Amrie Firmansyah (ZILLZELL MEDIA PRIMA, 2026)
This study examines the influence of professional skepticism and integrity on audit quality, with time budget pressure as a moderating variable, among external auditors working at Public Accounting Firms in Greater Jakarta. The research employs a quantitative approach with primary data collected through questionnaires distributed to 59 auditors. Data analysis was conducted using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4 software. The results indicate that professional skepticism does not significantly affect audit quality, suggesting that skeptical attitudes in this study reflect a more defensive orientation toward audit risk rather than contributing to quality improvement. Integrity has a significant positive effect on audit quality, confirming that auditors who uphold high integrity standards produce more reliable and credible audits. Time budget pressure does not moderate the relationship between professional skepticism and audit quality, nor between integrity and audit quality, indicating that internal auditor characteristics operate independently of time constraints. These findings highlight that integrity is a critical determinant of audit quality, while professional skepticism and time budget pressure play limited roles in the Indonesian audit context. The study contributes to the auditing literature by extending attribution theory to audit quality formation and provides practical implications for Public Accounting Firms in developing auditor integrity through ethics training and professional development programs.